2019
DOI: 10.3389/fimmu.2019.01947
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Alpha Antagonist Interferes With the Formation of Granulomatous Multinucleated Giant Cells: New Insights Into Mycobacterium tuberculosis Infection

Abstract: More than half of tuberculosis cases in the world are due to resuscitation of dormant Mycobacterium tuberculosis ( Mtb ) sequestered into cell-derived structures called granulomas. It is fairly admitted that cytokines and more particularly Tumor Necrosis Factor (TNF)-α is critical in the control of Mtb infections and that anti-TNF-α drugs constitute one of the main risk factors for reactivation of latent Mtb infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 72 publications
0
35
0
1
Order By: Relevance
“…TNF plays major roles in the granuloma formation and maintenance both in human TB and in animal models (22). It is produced by myeloid cells and Mtb-specific T cells within TB granulomas.…”
Section: Enhanced Susceptibility To Necrotizing Tb Granulomas In Sst1mentioning
confidence: 99%
“…TNF plays major roles in the granuloma formation and maintenance both in human TB and in animal models (22). It is produced by myeloid cells and Mtb-specific T cells within TB granulomas.…”
Section: Enhanced Susceptibility To Necrotizing Tb Granulomas In Sst1mentioning
confidence: 99%
“…It is unknown whether these MNGCs were fused by Bpm or, like the M. tuberculosis granuloma, they have become polyploid due to inflammation-induced DNA damage or cytokine influence [ 38 , 39 ] ( Figure 1 ). Studies have shown that peripheral blood mononuclear cells (PBMCs) exposed to beads coated in M. tuberculosis extract begin to form granulomas, including MNGCs, without live bacteria [ 45 ]. It is reasonable to speculate that the formation of MNGCs during M. tuberculosis infection is a passive process from the bacterial side.…”
Section: Role Of Mngcs In Diseasementioning
confidence: 99%
“…It is unknown whether these MNGCs house bacteria or, like M. tuberculosis, they have fused due to an unknown immunological stimulus (Figure 1). Studies have shown that peripheral blood mononuclear cell (PBMCs) exposed to beads coated in M. tuberculosis extract begin to form granulomas, including MNGCs, without live bacteria [39]. It is reasonable to speculate that the formation of MNGCs during M. tuberculosis infection is a passive process from the bacterial side.…”
Section: Role Of Mngcs In Diseasementioning
confidence: 99%